Scapular muscular activity with shoulder impingement syndrome during lowering of the arms - de Morais, F.; Danielli, C. C.; Fuscaldi, L.; de Paula, G.; Rodrigues, F.; de Souza, M.; Fabiano, G. (Clinical Journal of Sport Medicine, 2008)
Objective: To compare isolated electromyographic (EMG) activity of the serratus anterior, upper, middle, and lower trapezius, as well as the coactivation of the upper and middle trapezius/serratus anterior in subjects with and without shoulder impingement syndrome (IS), during lowering of the arms. Design: Cross-sectional study. Setting: University laboratory. Participants: Twenty young adults, 10 with unilateral IS degree I or II (mean age 28.6 +/- 5.89 years) and 10 without any complaints or history of previous shoulder lesions (mean age 29.0 +/- 5.35 years), matched by gender, age, and levels of physical activity. Main Outcome Measurements: Isolated EMG activity of the serratus anterior, upper, middle, and lower trapezius, as well as the coactivation of the upper trapezius and middle trapezius/serratus anterior. The EMG activity was quantified by root mean square calculations and normalized by maximal voluntary isometric contractions. Results: Significant differences between groups were found only for the coactivation of the middle trapezius/serratus anterior (F = 6.81; P = 0.02). No significant differences were found between sides (F = 0.05; P = 0.83) nor for interactions between sides and groups (F = 3.85; P = 0.07). Conclusions: These findings pointed out the importance of evaluating the lowering of the arms in individuals with IS and suggested that measures of coactivation, besides reflecting the real purpose of the muscular actions during functional activities, are more sensitive to detect changes between groups. The evaluation of the coactivation of the middle trapezius/serratus anterior should be included in clinical assessment of individuals with IS and investigations on the etiology and progression of IS.